(3GdehWCs - (3eGdc Hf CfS Hf eGdc GdCUHMj GdMejQj, CHh YHO Gddg, J (B179 (3g` s ((3eOjfI eQGcT s)
(3ChdgG (B:s
(3cJGH GdQLe eG LGA ai GdQMef MOKfi jMji Hf jMji Cfg bGd LGAJ GdjghO Edi QShd Gddg Udi Gddg Ydjg hSde aPcQhG Hg Cf QLdkG efge hGeQCI RfjG s
(3BNQgG (B:s
(3jfJgi HHGH GdJTejJ ai GdYWGS ef cJGH GdLGeY hBNQ eG ajg (B: (3hMOKfi Yf eGdc Yf fGaY Cf YHO Gddg Hf YeQ cGf EPG YWS abjd dg (B: (3jQMec Gddg bGd (B: (3jQMefG Gddg hEjGce hjZaQ dfG hdce s
(3GdfSNI HgG MhGTs
(3QhGjI jMji Hf jMji GddjKi (B234 (3fSNI Ydi Qb ZRGds
(3cJHJ dNRGfI Ydi Hf jhSa Hf JGTajf s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs